Supplementary methodological and clinical aspects - Eyding, Jens; Bartig, Dirk; Weber, Ralph; Hacke, Werner; Krogias, Christos (Deutsches Ärzteblatt, 2020)
Relapse and mortality rates were methodically evaluated on the basis of health insurance data, which—in contrast to purely register-based approaches—record individual courses even after inpatient treatment (1). As data from 2010/2011 were used, the...